Artificial synaptic device based on a multiferroic heterostructure. (3rd September 2019) - Lu, Pei-Pei; Shen, Jian-Xin; Shang, Da-Shan; Sun, Young
Abstract: A type of synaptic devices have been constructed by employing the nonlinear magnetoelectric effects in multiferroic materials. The state of the magnetoelectric coefficient of the device can be tuned continuously with a large number of nonvolatile levels by engineering the applied electric-field pulses. Therefore, the magnetoeletric coefficient may be regarded as the synaptic weight, and the subsequent magnetoelectric voltage V ME acts as excitatory or inhibitory postsynaptic potentials. Synaptic behaviors including the long-term potentiation, long-term depression, and spiking-time-dependent plasticity have been demonstrated in a multiferroic heterostructure made of Metglas/PMN-PT/Metglas. The consumed energy density is estimated to be ~7.7 mJ cm −3 per spike, comparable to the biological synapse in the brain. Our work presents an alternative way towards artificial synaptic devices with very low energy consumption.